Integrated handling to overcome stunting in rural areas in East Java, Indonesia - Septi Ariadi (Masyarakat, Kebudayaan dan Politik, 2023)
Stunting is one of the pressing health issues that requires serious attention and immediate intervention. This study aimed to assess the causes of stunting, the challenges faced by communities in ensuring nutrition for children, the management of stunting, and the efforts needed to optimize stunting intervention in rural areas. This study employed a qualitative approach with a total of 30 families having stunted children as informants. The study reveals that preventive measures against stunting should commence early, even during pregnancy. Apart from nutritional deficiencies, equally important contributing factors are inadequate maternal knowledge, recurrent or chronic infections, poor sanitation, and limited healthcare access. One pivotal step in preventing stunting is empowering and centralizing the role of mothers, who should be committed actors in the stunting prevention process. In a child’s growth and development, exclusive breastfeeding along with appropriate complementary feeding demands attention. Understanding child growth stages is crucial for parents to prevent stunting. Although most parents are aware of the significance of meeting their child’s nutritional needs, economic constraints and lack of awareness still hinder some parents from giving extra attention to this matter.